The Revitalisation of Planning Education in Africa: A Review of Planning Education at the Catholic University in Beira, Mozambique (The Journal of Building and Land Development, 2018)
Planning education at the Catholic University of Mozambique consists of undergraduate and post graduate programmes. These programmes aim to provide an overall understanding of the human-environment nexus by addressing physical, economic and human development needs as well as proposing appropriate and effective planning for different regions. The programmes are also part of the institution‟s way of complementing government efforts of decentralization by building the requisite manpower targeted for policy implementation. Of the post-graduate studies, the MSc in Regional Development Planning was introduced in February 2008 while the MSc in Geographic Information Systems (GIS) began in March 2009. In March 2010, the University will introduce a BSc Honours in Regional, District and Town Planning programme. The need to focus education towards development and planning was necessitated by the government‟s emphasis on decentralisation in planning and management of districts and noted uneven regional development between the north and south of the country. This noted uneven development then entailed the need for capacity building in the planning profession. This paper gives an overview of planning programmes at the Catholic University of Mozambique, Beira. It outlines economic, socio-political and physical environment within which programmes are offered in Mozambique as well as Beira City. Major challenges faced in delivering these programmes are highlighted. It concludes by outlining how regional development and planning programmes in the 21st Century are designed to equip graduates for employment in development oriented research, planning, education and management in both public and private sectors where they can contribute meaningfully to sustainable regional development.